74.3k views
1 vote
PLEASE HELP ME IM BEGGING IM REALLY STRUGGLING

PLEASE HELP ME IM BEGGING IM REALLY STRUGGLING-example-1
User Mzuba
by
4.1k points

2 Answers

4 votes

Answer:

The solution is the triplet: (a, b, c) = (-3, 0, 0)

Step-by-step explanation:

Let's start with the second equation, and solving for "a":

a - b = -3

a = b - 3

Now replace this expression for a in the third equation:

2 a + b = -6

2 (b - 3) +b = -6

2 b - 6 +b = -6

3 b = -6 +6

3 b = 0

b = 0

So if b = 0 then a = 0 - 3 = -3

now we can replace a= -3, and b = 0 in the first equation and solve for c:

2 a - b + c = -6

2 ( -3) - 0 + c = -6

-6+ c = -6

c = -6 + 6

c = 0

Our solution is a = -3, b= 0 , and c = 0 which can be expressed as (-3, 0, 0)

User Zanshin
by
4.5k points
3 votes

Answer:

I hope it will help you.....

PLEASE HELP ME IM BEGGING IM REALLY STRUGGLING-example-1
User Dhanushka
by
5.2k points